Unraveling the mechanism of l-gulonate-3-dehydrogenase inhibition by ascorbic acid: Insights from molecular modeling. (December 2018) - Agrawal, Nikhil; Hossain, Md. Summon; Skelton, Adam A.; Muralidhar, Kambadur; Kaushik, Sandeep
Graphical abstract: Legend: Ascorbic acid (white) has steric clashed with NADH (orange) and leads to gulonate-3-dehydrogenase inhibition. Highlights: Molecular dockings of ascorbate to gulonate-3-dehydrogenase indicated its binding near the co-factor binding site. Docking revealed that ascorbate binding could lead to steric clashes between ascorbate and the co-factor (NADH). Molecular dynamics simulations confirm interaction of ascorbic acid at the co-factor binding site. Ascorbate's binding negatively affects further binding of NADH to and enzymatic functions of gulonate-3-dehydrogenase. These observations depict a possible mechanism of gulonate-3-dehydrogenase inhibition by ascorbic acid. Abstract: l -Gulonate dehydrogenase (GuDH) is a crucial enzyme in the non-phosphorylated sugar metabolism or glucuronate-xylulose (GX) pathway. Some naturally occurring compounds inhibit GuDH. Ascorbic acid is one of such inhibitors for GuDH. However, the exact mechanism by which ascorbic acid inhibits GuDH is still unknown. In this study, we try to investigate GuDH inhibition using computational approaches by generating a model for buffalo GuDH. We used this model to perform blind dockings of ascorbic acid to GuDH. Some docked conformations of ascorbic acid bind near Asp39 and have steric clashes with crystal structure conformation of NADH. To assess the dynamic stability of the GuDH-ascorbic acid complex, we performed six molecular dynamics simulations for GuDH, three each in its free form and in complex with ascorbic acid for 50 ns, to obtain 300 ns of trajectories in total. During the simulations, ascorbic acid interacted with several residues nearby Asp39. As Asp39 is an important residue for NADH binding and specificity, the interaction of ascorbic acid near Asp39 hinders further NADH binding and ultimately affects the enzymatic functioning of GuDH. In this study, we analyze these interactions between ascorbic acid and GuDH. Our analysis reveals novel details on the mechanism of GuDH inhibition by ascorbic acid.